Key concepts in cinema - Hayward, Susan (Routledge, 1996)
Key Concepts in Cinema Studies is a comprehensive glossary of the main terms and concepts in film theory and film production. The book includes definitions of key film genres, from Westerns to Musicals; major movements of world cinema, from New German Cinema to Third Cinema; theories used in the study of cinema, from auteur theory to psychoanalysis and to feminist film theory; and key film production terms, from film editing to zoom lens.